LPS-induced MMP-9 expression is mediated through the MAPKs-AP-1 dependent mechanism in BEAS-2B and U937 cells. (28th May 2018) - Tian, Xue; Xie, Guogang; Ding, Fengming; Zhou, Xin
Abstract: Aim of the Study: Matrix metalloproteinases (MMPs) play a critical role in chronic obstructive pulmonary disease (COPD). This study investigated the role of mitogen-activated protein kinases (MAPKs) in MMP-9 secretion of BEAS-2B cells, a human bronchial epithelial cell line and U937 cells, a human myeloid leukaemia cell line, which could differentiate into macrophage, after LPS stimulation, and some details of involved signaling. Materials and Methods: MTT assay was used to measure cell viability. U937 cells were incubated for 48h with 100ng/ml PMA, and had a resting period of 24h with culture medium without PMA for differentiation of U937 cells into macrophages. For the experiments, U937 cells or BEAS-2B cells were pretreated with several inhibitors and then stimulated by LPS. Western blotting, quantitative real-time PCR, enzyme-linked immunosorbent assay (ELISA) and DNA binding activity assay were used for measuring the protein expression, RNA expression, cytokine production and DNA binding activity, respectively. Results: We found LPS induced MMP-9 expression and secretion were completely blocked by stress-activated protein kinase/jun kinase (SAPK/JNK) and extracellular signal-regulated kinase 1/2 (ERK1/2) inhibitors but not by p38 inhibitor. LPS-induced transactivation of AP-1 was also inhibited by JNK inhibitor SP600125 and ERK1/2 inhibitor PD98059. Conclusions: The present study suggests that in BEAS-2B cells and U937 cells, LPS probably activates ERK1/2 pathway and JNK pathway, which in turn initiate AP-1 activity, and leading to MMP-9 expression. Thus the ERK1/2 inhibitor and JNK inhibitor may have potential clinical value in treating COPD.